Contextualizing Genetics: A Meta-Analysis of Academic Achievement through Context-Based Teaching - Charles Amoah Agyei; Maxwell Gyamfi (Journal of Research in Education and Pedagogy, 2026)
This meta-analysis investigates the effectiveness of context-based teaching approaches on students’ academic achievement in genetics, a subject often perceived by learners as abstract and cognitively challenging. Traditional instruction in genetics tends to emphasize memorization over meaningful understanding, contributing to widespread disengagement and underperformance. In response, educational reform efforts have increasingly promoted context-based teaching, which situates learning within real-world scenarios to improve relevance, comprehension, and learner motivation. The objective of this study was to quantify the impact of context-based instruction on academic achievement in genetics by synthesizing data from 69 master’s and doctoral theses conducted between 2010 and 2022. These studies were selected based on stringent inclusion criteria: use of experimental or quasi-experimental designs, focus on genetics education, availability of relevant statistical data, and application of context-based instructional strategies. A total sample of 4,790 students was analyzed, 2,476 in experimental groups and 2,314 in control groups. Effect sizes were calculated using Comprehensive Meta-Analysis (CMA) software, applying both fixed-effect and random-effect models. The results demonstrated large and statistically significant positive effects of context-based instruction on student achievement in genetics (FEM d = 0.789; REM d = 1.064), with substantial heterogeneity observed across studies. These findings underscore the pedagogical value of integrating real-life contexts into genetics education. The study concludes that context-based instruction significantly enhances students’ understanding and performance in genetics. It highlights the need for teacher training, curriculum reform, and instructional design that aligns with constructivist principles. While limitations exist, such as the exclusive reliance on theses and language restrictions, the study provides a strong foundation for future research and evidence-based policy in science education.